How to survive middle school - Gephart, Donna (Yearling, 2011)
When thirteen-year-old David Greenberg's best friend makes the start of middle school even worse than he feared it could be, David becomes friends with Penny, who shares his love of television shows and posts one of their skits on YouTube, making them wildly popular--online, at least.